Effects of platelet-rich plasma in association with bone grafts in maxillary sinus augmentation: A systematic review and meta-analysis - Lemos, C. A.A. [UNESP] (2016)
This systematic review evaluated the effect on bone formation and implant survival of combining platelet-rich plasma (PRP) with bone grafts in maxillary augmentation. A comprehensive review of articles listed in the PubMed/MEDLINE, Embase, and Cochrane Library databases covering the period January 2000 to January 2015 was performed. The meta-analysis was based on bone formation for which the mean difference (MD, in millimetres) was calculated. Implant survival was assessed as a dichotomous outcome and evaluated using the risk ratio (RR) with 95% confidence interval (CI). The search identified 3303 references. After inclusion and exclusion criteria were applied, 17 studies were selected for qualitative analysis and 13 for quantitative analysis. A total of 369 patients (mean age 51.67 years) and 621 maxillary sinus augmentations were evaluated. After the data analysis, additional analyses were performed of the implant stability quotient, marginal bone loss, and alveolar bone height measured by MD. The results showed no significant difference in implant stability (P = 0.32, MD 1.00, 95% CI -0.98 to 2.98), marginal bone loss (P = 0.31, MD 0.06, 95% CI -0.05 to 0.16), alveolar bone height (P = 0.10, MD -0.72, 95% CI -1.59 to 0.14), implant survival (P = 0.22, RR 1.95, 95% CI 0.67-5.69), or bone formation (P = 0.81, MD -0.63, 95% CI -5.91 to 4.65). In conclusion, the meta-analysis indicates no influence of PRP with bone graft on bone formation and implant survival in maxillary sinus augmentation.